Knowledge of learning disabilities among pre-service and in-service trainee teachers in Malaysia - Saad, Supiah; Ismail, Khamsiah; Abd Hamid, Siti Rafiah (IIUM Press, 2014)
Are mainstream teachers in Malaysia knowledgeable about types of students with special needs? Are there enough support services as well as facilities provided for these students’ education? This study investigated the knowledge level of Malaysian in-service trainee teachers undergoing a distance learning Bachelor of Education program sponsored by the Malaysian Ministry of Education and pre-service trainee teachers enrolled in a regular bachelor of education program. The sample consisted of 296 students of bachelor degrees at two public universities, 39 males and 257 females; 147 in-service student teachers and 149 pre-service student teachers. The respondents completed a 36-item survey designed by the researchers, which had adequate psychometric properties. The results of the study revealed that student teachers had a rich level of knowledge on a few aspects of learning disabilities and a moderate level of knowledge in other aspects tested. In-service student teachers were found to be more knowledgeable than pre-service student teachers. Student teachers’ level of knowledge was not related to their age and teaching experience. However their level of knowledge was somehow related to their status. Mass media were the main sources of information for both groups of trainee teachers. The implications of these findings for inclusive education and for future research are discussed.